Emerging Issues and Models in College Mental Health Services. Issue 156 (7th December 2016) - Locke, Ben; Wallace, David; Brunner, Jon
Abstract : This chapter provides a brief overview of the psychological issues facing today's college students, information about students receiving mental health services, and an evidence‐based model describing the practice and functions of today's counseling centers.